Effect of magnetic nanoparticles of Fe3O4 and wogonin on the reversal of multidrug resistance in K562/A02 cell line - Cheng J (Dove Medical Press, 2012)
Jian Cheng,1,* Lin Cheng,1,* Baoan Chen,1,2 Guohua Xia,1 Chong Gao,1 Huihui Song,1 Wen Bao,1 Qinglong Guo,3 Haiwei Zhang,3 Xuemei Wang41Department of Hematology, Key Medical Disciplines of Jiangsu Province, Zhongda Hospital, Medical School of Southeast University, 2Department of Oncology of Southeast University, 3Key Laboratory of Carcinogenesis and Intervention of Jiangsu Province, China Pharmaceutical University, 4State Key Laboratory of Bioelectronics, Southeast University, Nanjing, People's Republic of China *These authors contributed equally to this workBackground: Multidrug resistance is the main obstacle to the efficiency of systemic chemotherapy against hematologic malignancy. This study investigated the reversible effect of the copolymer wogonin and daunorubicin coloaded into Fe3O4 magnetic anoparticles, and the mechanism potentially involved.Methods: The growth inhibition rate of K562/A02 cells was investigated by MTT assay, and apoptosis of cells and the intracellular daunorubicin concentration were detected by flow cytometry. Distribution of nanoparticles taken up by K562/A02 cells was observed under a transmission electron microscope and demonstrated by Prussian blue staining. The transcription level of MDR1 mRNA and expression of P-glycoprotein were determined by reverse transcriptase polymerase chain reaction and Western blotting assay, respectively.Results: The reversible effect of daunorubicin-wogonin magnetic nanoparticles was 8.87-fold that of daunorubicin + wogonin and of daunorubicin magnetic nanoparticles. Transmission electron microscopy and Prussian blue staining revealed that the nanoparticles were located in the endosome vesicles of cytoplasm. Also, the apoptosis rate and accumulation of intracellular daunorubicin in the daunorubicin-wogonin magnetic nanoparticle group were significantly higher than that in the daunorubicin, daunorubicin + wogonin, and daunorubicin magnetic nanoparticle groups. Furthermore, transcription of MDR1 mRNA and expression of P-glycoprotein in K562/A02 cells were significantly downregulated in the daunorubicin-wogonin magnetic nanoparticle group compared with the other groups.Conclusion: These findings suggest that the remarkable effects of the novel daunorubicin-wogonin magnetic nanoparticle formulation on multidrug resistant K562/A02 leukemia cells would be a promising strategy for overcoming multidrug resistance.Keywords: magnetic nanoparticles, Fe3O4, wogonin, multidrug resistance, daunorubicin, P-glycoprotein